TRANSFORMATION OF HUMAN NATURE IN THE CONTEXT OF THE "MAN-NATURE" SYSTEM - Drotianko, Liubov (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Since the late 60’s of the twentieth century, scientists and philosophers have talked about the survival of mankind through the irrational activities of people in nature. Since then, a thorough study of the problem of the relationship of man and society to the biosphere began in the natural sciences, in interdisciplinary fields, and in social sciences. In the XXI century, the technological activity of people in a technogenic civilization is significantly expanding beyond the Earth’s atmosphere, which encourages a philosophical understanding of the processes of further technologicalization of the biosphere and near space. The aim and tasks is to identify positive and negative trends in the transformation of human nature in the context of the system of "man-nature" in the deepening global environmental crisis. Research methodology. Leading methodological tools of the research are: a systemic methodological approach, which allows for analysis of the unity of nature and man as a representative of the species Homo sapiens in a holistic system of "naturesociety"; a socio-cultural methodological approach that helps to identify socio-cultural factors that influence the transformation of human nature; an interdisciplinary methodological approach, which allows taking into account both philosophical and scientific views on the problem of transformation of human nature in the context of exacerbation of the global environmental crisis. Research results. The article considers the impact of technological activities of society on the biological state of man, as it adapts to changing natural conditions of everyday life. However, other factors have a significant impact on the transformation of human nature. In particular, the intervention in human nature through the use of biotechnology; the use of pharmacological drugs that enhance physiological endurance; gender reassignment surgery, etc is demonstrated. It is shown that such interference in the biological nature of man leads to the transformation of his socio-cultural nature. Questions for discussion by the philosophical and scientific community have been formulated. Discussion The problems related to the research in the article, which arises in the context of the system "man - society", are studied. In particular, those outlined in the articles by G.M. Kleshny, S.S. Ordenov, I.P. Skiba, O.P. Skiba, and T.H. Shorina, published in the professional publication "Proceedings of the National Aviation University. Series: Philosophy. Cultural Studies", no 2 (34) for 2021. Conclusions. The article considers only some aspects of the problem of transformation of human nature in the context of the system "man-nature". It is shown that the main current risks in this system lie in the application of modern biotechnology, the latest information and communication tools, pharmacological agents, and more.